Antimicrobial evaluation of some synthesized Flavone derivative compounds - Raut2, Vikram Patil1, B.Y. Gotigalla1, S.D. (International Multidisciplinary Research Journal, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The antibacterial evaluation of flavone derivative compounds was done against pathogenic micro-organisms. For the antibacterial activity against, four human pathogens namely, Bacillus subtilis, Proteus vulgaris and Escherichia coli and one plant pathogen, Pseudomonas auroginosa were selected. Antibacterial activity was tested by well method. Most of these compounds showed antibacterial activity against these selected pathogenic microorganisms. The MIC (Minimal Inhibition Concentration) of the flavones derivative was also tested against the above pathogens. The antifungal activity of flavones derivative were tested against four pathogenic fungi namely Alternaria sp. and Helminthosporium sp., Aspergilus niger and A. flavus. The antifungal activity was tested by well method. Most of these compounds showed antifungal activity. <div style="border-right: medium none; border-top: medium none; margin-left: 34pt; border-left: medium none; margin-right: 34pt; border-bottom: windowtext 1pt solid; mso-element: para-border-div; mso-border-bottom-alt: solid windowtext .5pt; padding: 0in;"> Keywords: Flavones, Antibacterial, Antifungal